Exercise During Work Hours Improves Fitness: An Evidence-Based Case Report - Afid Brilliana Putra; Rara Maasnika Adham; Febrina Alivia Wantania; Amy Grace Yulita; Listya Tresnanti Mirtha (Fakultas Kedokteran Universitas Riau, 2024)
Relatively tight working hours are problems for employees in urban areas, affecting less time for physical activities. About 59% of office workers in Jakarta are classified as sedentary. The high number of sedentary workers can cause productivity problems due to low fitness. Appropriate interventions are needed to overcome it. We have done literature searches from 7 journal databases in the last 20 years, including ScienceDirect, EBSCOhost, PubMed, ProQuest, Scopus, ClinicalKey, and Cochrane. Inclusion criteria include research design in the form of systematic review/meta-analysis/randomized controlled trials, outcomes in the form of physical fitness or work performance, and interventions in the form of workplace exercise or stretching. Three selected articles showed a significant relationship (p-value <0.05) between programmed physical exercise at work and several fitness factors, such as decreased body fat and fat mass, increased lean mass, and increased sit-up and push-up fitness test results. Physical activity at work decreased cardiovascular risk as assessed by VO2max. In conclusion, physical activity during working hours effectively improves health-related fitness. The minimal intervention types needed are aerobics, strength training, and muscle endurance. We recommend providing interventions for workplace fitness and education programs (WFEP).